2020
DOI: 10.1021/jacs.0c08390
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanistic Insights into the Formation of Imine-Linked Two-Dimensional Covalent Organic Frameworks

Abstract: A more robust mechanistic understanding of imine-linked two-dimensional covalent organic frameworks (2D COFs) is needed to improve their crystalline domain sizes and to control their morphology, both of which are necessary to fully realize their application potential. Here, we present evidence that 2D imine-linked COFs rapidly polymerize as crystalline sheets that subsequently reorganize to form stacked structures. Primarily, this study focuses on the first few minutes of 1,3,5-tris­(4-aminophenyl)­benzene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 50 publications
6
102
0
Order By: Relevance
“…As the observed sheets were very thin, it was suggested that COFs might initially crystallize as disordered sheets, followed by a recrystallization to ordered and porous powder. 118 Moreover, equilibration of these 60 seconds samples in supercritical CO 2 (scCO 2 ) for 72 hours led to crystalline peaks as observed by PXRD. The difference between both proposed mechanism is illustrated in Fig.…”
Section: Mechanism Of Imine Cof Formationmentioning
confidence: 94%
“…As the observed sheets were very thin, it was suggested that COFs might initially crystallize as disordered sheets, followed by a recrystallization to ordered and porous powder. 118 Moreover, equilibration of these 60 seconds samples in supercritical CO 2 (scCO 2 ) for 72 hours led to crystalline peaks as observed by PXRD. The difference between both proposed mechanism is illustrated in Fig.…”
Section: Mechanism Of Imine Cof Formationmentioning
confidence: 94%
“…And the large number of amine and aldehyde linkers made imine-linked COFs to be the most popular strategy to synthesize COF. [41][42][43] Wang et al reported a 2D COF (COF-LZU1) linked by condensation reaction of 1,4-diaminobenzene and 1,3,5-tricarbonylbenzene (Figure 2b). [44] The as-synthesized COF-LZU1 showed extremely high stability in common organic solvents and water.…”
Section: The Construction Of 2d Cofsmentioning
confidence: 99%
“…Research showed these imine‐bonded 2D COFs possessed higher stability in water. And the large number of amine and aldehyde linkers made imine‐linked COFs to be the most popular strategy to synthesize COF [41–43] . Wang et al reported a 2D COF (COF‐LZU1) linked by condensation reaction of 1,4‐diaminobenzene and 1,3,5‐tricarbonylbenzene (Figure 2b) [44] .…”
Section: The Construction Of 2d Cofsmentioning
confidence: 99%
“…28 The COF polymerization process has been studied by Marder and co-workers, and they found that the disordered thin, crystalline COF layers form within the aggregates at the very early stage of the COF polymerization. 16 Though this work was performed with imine COFs, these principles appear to be relevant in the case of hydrazone COFs as well as hydrazone COFs, when carefully activated, retain their crystalline structure. The nature of the loss of crystallinity upon activation is less clear, especially since we have observed it with hydrazone COFs that are similar to those known to readily delaminate in polar solvent 18 (TFPT-DHz and TFPB-DHz COFs) as well as Py-DHz COF which is made with a tetraphenylpyrene monomer that is well-known to form highly correlated stacking interactions in 2D-COFs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These materials have been employed for various applications including catalysis, 8 gas storage, 9 gas separations, 10 energy storage, 11 and sensing 12 due to their promising properties such as well-defined structures, 3,13 high surface area, 9 tunable pore size, 14 and low density. 9 The general mechanisms of COF polymerization and assembly have received considerable attention over the past few years 15,16 in order to help researchers understand why certain combinations of monomers form crystalline COFs over others. Hydrazone-based COFs have been studied extensively due to their physicochemical stability compared to imine, or boronate ester linked COFs.…”
Section: Introductionmentioning
confidence: 99%